Perbandingan Metode AHP dan SAW Untuk Menentukan Dosen Berprestasi - Debby Ummul Hidayah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The selection of outstanding lecturers in an Information Systems study program at XYZ University is currently still done conventionally. That is, it is still subjective and has not used special calculation methods to support decisions. Thus, it is necessary to have an appropriate decision support system to assist in determining outstanding lecturers objectively. The method used in this research is the analytical hierarchy process (AHP) and simple additive weighting (SAW). From the calculation of the two methods, the final result is a decision to select an outstanding lecturer in the same Information Systems study program, namely Mr. Argiyan Dwi Pritama. The results obtained from the AHP calculation yield a value of 1.46 while the SAW calculation produces a value of 0.522. From the AHP calculation, it can be concluded that the use of too many alternatives makes the ranking process too complex. Meanwhile, based on the SAW calculation, the technical calculation is very suitable for many alternatives, so it is more effective and efficient to use.